Arab - Islamic culture and its relationship to education - Ferroum, Hicham; Berkani, Rida (Milev Journal of Research and Studies, 2019)
Man is the creator, bearer and carrier of culture from generation to generation. This will not be done in isolation from education, which is part of the culture of society, but the various processes that enable culture to continue and develop are educational educational processes, in the sense that education is the backbone of culture. Culture is the spirit of education. Therefore, we must understand the successful methods and methods of education that lead us to preserve our identities and the roots of our societies and without erosion and extinction, through the creation of a generation imbued with the Arab-Islamic culture.